Detection of mobile colistin-resistance gene variants (mcr-1 and mcr-2) in urinary tract pathogens in Bangladesh: the last resort of infectious disease management colistin efficacy is under threat - Ara, Bayasrin; Urmi, Umme Laila; Haque, Tanjum Ara; Nahar, Shamsun; rumnaz, Adity; Ali, tamanna; Shah Alam, Mohammed; Md. Mosaddek, Abu Syed; A. Rahman, Nor Azlina; Haque, Mainul; Islam, Salequl (Taylor & Francis Group, 2021)
Background: Currently, colistin-resistant pathogens emerged has become a global health concern. This study assessed the distribution of mcr-1 to mcr-5 variants with the phenotypic colistin-resistance in bacterial isolates from urinary tract infection (UTI) patients in Bangladesh. Methods: A cross-sectional study was conducted between April 2017 and March 2018 to enroll uncomplicated UTI patients, and 142 urine samples were analyzed. Uropathogens were identified using the API-20E biochemical panel and 16s rRNA gene sequencing. Polymerase chain reactions detected the mcr gene variants in the UTI isolates. The phenotypic colistin-susceptibility was determined by the Kirby–Bauer disc-diffusion method and the minimal inhibitory concentration (MIC) measurement. Results: The combined carriage of mcr-1 and mcr-2 genes in 11.4% (14/123) of urinary tract pathogens. The mcr-positive pathogens include five Escherichia coli, three Klebsiella pneumoniae, three Pseudomonas putida, two Enterobacter cloacae, and one Enterobacter hormaechei. The mcr-positive variant showed significantly higher phenotypic colistin resistance with MIC between >16 μg/mL and >128 μg/mL (p< 0.001). Over 85% of colistin-resistant isolates showed MDR phenomena. Conclusions: The emergence of the clinical MDR pathogens with resistance to a highly selective drug may lead to a lack of treatment options for the infectious diseases and spread of infection to the unaffected cohorts.